2005
DOI: 10.1149/1.1895285
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties in High-k HfO[sub 2] Capacitors with an Equivalent Oxide Thickness of 9 Å on Ru Metal Electrode

Abstract: HfO 2 films with an EOT of 9 Å were deposited at 300°C on Ru/TiN/SiO 2 /Si substrates using an atomic layer deposition technique and the electrical properties of Ru/HfO 2 /Ru capacitors were investigated as a function of the film thickness and annealing temperature. The dielectric constant, dielectric loss, and leakage current density at 1.0 V in the films with a thickness of 7 nm were ϳ19, 0.9 %, and 8 ϫ 10 −7 A/cm 2 , respectively. The capacitors show the stable electrical properties in a thermal treatment u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The variation of the SBH of Ni/ZrO 2 interfaces was found to be as large as 0.76 eV depending upon the surface structure of the dielectric. Much effort has been focused on refining and optimizing metal/dielectric structures to meet engineering requirements. Various experimental studies have been published within the past few years focusing on the electrical properties of Ru/HfO 2 systems. However, the structural and chemical nature of the metal/dielectric interface have largely remained unknown due to the complexity of metal/dielectric interfacial structures and the lack of experimental probes for in situ atomic-scale characterization of buried interfaces. Atomistic modeling offers microscopic insight into otherwise inaccessible aspects of complex interface structures.…”
Section: Introductionmentioning
confidence: 99%
“…The variation of the SBH of Ni/ZrO 2 interfaces was found to be as large as 0.76 eV depending upon the surface structure of the dielectric. Much effort has been focused on refining and optimizing metal/dielectric structures to meet engineering requirements. Various experimental studies have been published within the past few years focusing on the electrical properties of Ru/HfO 2 systems. However, the structural and chemical nature of the metal/dielectric interface have largely remained unknown due to the complexity of metal/dielectric interfacial structures and the lack of experimental probes for in situ atomic-scale characterization of buried interfaces. Atomistic modeling offers microscopic insight into otherwise inaccessible aspects of complex interface structures.…”
Section: Introductionmentioning
confidence: 99%
“…However high leakage current of this type of high-k compared to HfO 2 , ZrO 2 , and Al 2 O 3 should be suppressed for being used widely. It was reported that high work function noble metal electrodes have been used to improve the interface-controlled leakage current [5]. In this study, high work function Ru was considered as electrodes and low band gap property of these high-k dielectrics was engineered by the manufacturing methods like doping and multi-layer etc.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown to be a suitable insulator in metal-insulator-metal (MIM) capacitor devices, although it is susceptible to recrystallization after high temperature processing (14). It has also been reported that the electrical and thermal stability properties of HfO x films are significantly improved by the addition of Al oxide to the hafnia film (15)(16)(17)(18)(19)(20)(21). AlO x is known for its stable thermal and electrical properties; however, it possesses a relatively low dielectric constant of ~8.…”
Section: Introductionmentioning
confidence: 99%